Safety of a feed additive consisting of indigo carmine for cats, dogs and ornamental fish (Sensient Colors Europe GmbH) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety of indigo carmine as a colourant feed additive for cats, dogs and ornamental fish. In its previous opinion, the FEEDAP Panel concluded that indigo carmine is safe for cats and dogs at levels up to 250 mg/kg complete feed and for ornamental fish up to 1000 mg/kg complete feed. These conclusions were limited to indigo carmine with a purity of at least 93% colouring matter. For the current assessment, the applicant submitted additional data on the characterisation and on the toxicological profile to support the safety of the additive with the purity of at least 85% colouring matter. Based on the new data submitted, the FEEDAP Panel concludes that indigo carmine (purity of at least 85% colouring matter) is safe for cats and dogs at levels up to 250 mg/kg complete feed and for ornamental fish up to 1000 mg/kg complete feed.